ANALISIS SUSUT ENERGI PADA TEGANGAN RENDAH DI WILAYAH PT. PLN (PERSERO) AREA BULUNGAN - Zalmadi Syamsudin; Erlina Erlina; Heri Suyanto (Sekolah Tinggi Teknik - PLN, 2015)
In the distribution of electrical energy from the power plant to the consumer occurs energy loss or shrinkage energy. Losses of energy in a electrical system must always exist. This is due to the content of prisoners on permanent conductor and the nature of the network itself. In the process of calculating the energy losses experienced many difficulties because of the extensive distribution network. So we need a method to calculate the shrinkage. By performing measurements on distribution substations and calculate the voltage drop across the channel as well as custody and subsequently look for peak power losses and average power losses. Next calculate the energy is channeled so that it can calculate energy losses.